Nanotopography Induced Human Bone Marrow Mesangiogenic Progenitor Cells (MPCs) to Mesenchymal Stromal Cells (MSCs) Transition - Antonini, Sara; Montali, Marina; Jacchetti, Emanuela; Meucci, Sandro; Parchi, Paolo D.; Barachini, Serena; Panvini, Francesca M.; Pacini, Simone; Petrini, Iacopo; Cecchini, Marco (Frontiers in Cell and Developmental Biology, 2016)
Mesangiogenic progenitor cells (MPCs) are a very peculiar population of cells present in the human adult bone marrow, only recently discovered and characterized. Owing to their differentiation potential, MPCs can be considered progenitors for mesenchymal stromal cells (MSCs), and for this reason they potentially represent a promising cell population to apply for skeletal tissue regeneration applications. Here, we evaluate the effects of surface nanotopography on MPCs, considering the possibility that this specific physical stimulus alone can trigger MPC differentiation toward the mesenchymal lineage. In particular, we exploit nanogratings to deliver a mechanical, directional stimulus by contact interaction to promote cell morphological polarization and stretching. Following this interaction, we study the MPC-MSC transition by i. analyzing the change in cell morphotype by immunostaining of the key cell-adhesion structures and confocal fluorescence microscopy, and ii. quantifying the expression of cell-phenotype characterizing markers by flow cytometry. We demonstrate that the MPC mesengenic differentiation can be induced by the solely interaction with the NGs, in absence of any other external, chemical stimulus. This aspect is of particular interest in the case of multipotent progenitors as MPCs that, retaining both mesengenic and angiogenic potential, possess a high clinical appeal.